Infective endocarditis - a challenge for modern medicine. Review - Dobrzyński, Michał; Czarnota, Jakub; Skubel, Tomasz; Rybak, Natalia (Journal of Education, Health and Sport, 2022)
Infective endocarditis (IE) is defined by a focus of infection within the heart and is a feared disease across the field of cardiology. Prevalence varies from country to country, remaining in the range of 3-10/100 000 a year. Despite optimal care, mortality approaches 30% at 1 year. With an ageing population and increasing use of implantable cardiac devices and heart valves, the epidemiology of IE has changed. The microbiology of the disease has also changed, and staphylococci, most often associated with health-care contact and invasive procedures, have overtaken streptococci as the most common cause of the disease. The main lesions of IE are vegetations which cause emboli and destruction of valvular and/or perivalvular tissues leading to acute valvular regurgitations. Two main treatment pathways include antibiotic therapy and surgery The key to choosing the correct and most effective path is early diagnosis. The challenges posed by infective endocarditis are significant and therefore need further evaluation.